RansomListener: Ransom call sound investigation using LSTM and CNN Architectures - Rahman, Rafeed; Rahman, Mehfuz A; Hossain, Shahriar; Hossain, Sajid (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2020.